1983
DOI: 10.1007/bf02617992
|View full text |Cite
|
Sign up to set email alerts
|

Primary culture of normal pituitary cells of carp (cyprinus carpio) for the study of gonadotropin release

Abstract: A method for preparing enzymatically dispersed pituitary cell cultures of carp (Cyprinus carpio) is described. The cultures have been used to assay a synthetic analog of gonadotropin releasing hormone (GnRH) and to determine the specificity of steroids able to affect gonadotropin (GtH) release in vitro. Time course secretion studies indicated that by 48 h incubation, in the presence of 500 pM GnRH, cumulative secretion of gonadotropin (719 ng +/- 90/2.5 X 10(5) cells) had exceeded that of controls (446 ng +/- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1986
1986
1993
1993

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Recently pituitary fragments in a perifusion system have been described in goldfish (Mackenzie et al, 1984). The use df dispersed pituitary cells of the whole pituitary has been also reported either in short-term incubation (rainbow trout: Fihraeus-van Ree et al, 1982a,b) or in primary culture in a static model (rainbow trout: Fkhraeusvan Ree et al, 1982b; carp: Ribeiro and Ahne, 1982;Ribeiro et al, 1983) and in a perifusion system (goldfish: Chang et al, 1984). Recently a primary culture of purified pituitary gonadotrophs have been set up for African catfish (Leeuw et al, 1984).…”
Section: Dlscusslonmentioning
confidence: 99%
“…Recently pituitary fragments in a perifusion system have been described in goldfish (Mackenzie et al, 1984). The use df dispersed pituitary cells of the whole pituitary has been also reported either in short-term incubation (rainbow trout: Fihraeus-van Ree et al, 1982a,b) or in primary culture in a static model (rainbow trout: Fkhraeusvan Ree et al, 1982b; carp: Ribeiro and Ahne, 1982;Ribeiro et al, 1983) and in a perifusion system (goldfish: Chang et al, 1984). Recently a primary culture of purified pituitary gonadotrophs have been set up for African catfish (Leeuw et al, 1984).…”
Section: Dlscusslonmentioning
confidence: 99%
“…However, the authors do not specify the exact number of cells found and they worked on immature fish, in which it has now been well established that testosterone has a positive action on pituitary (for review, see . The only work performed on adult fish, using cultured pituitary cells treated with steroids, was conducted on pooled male and female carps and the authors did not specify the effect of the steroid treatments on cell number (Ribeiro et al, 1983).…”
Section: Gnrh-inducedmentioning
confidence: 99%
“…In vitro studies have also shown that GnRH is able to release GtH from perifused pituitary fragments and dispersed pituitary cells of goldfish , and from cultured dispersed pituitary cells of carp (Ribeiro et al, 1983) and rainbow trout (Weil et al, 1986).…”
Section: Introductionmentioning
confidence: 99%